Complejidad y participación: la senda de la invención estratégica - Martínez López, Miguel (Política y Sociedad, 2007)
The epistemological basis of research-participative action in the so-called «paradigm of complexity» is plagued with misconceptions, imprecision and significant omissions. The appropriate and contextualised translation of concepts acquired from natural sciences for use in social sciences is particularly necessary in qualitative-structural and participative-dialectic methodological trends. This study focuses on the concepts of «entropy», «complexity» and «strategic action». Based on a general notion of complexity relating to the consideration of uncertainty, innovation and the contextualisation of systems, we may highlight the performance-related aspects indicative of actions implied by this paradigm. Thus, the authors argue that the conceptualisation of operations such as «acting in order to know» and «act knowing/know by acting», encompassed in the notion of «strategic invention», complement or exceed the scope of typical planning operations and even self-planning («knowing in order to act»). In short, the authors argue that these definitions are coherent with an ecosystemic perspective of the social and natural reality, where it is necessary to contextualise what is more or less complex in the world, in our knowledge of the world and in our practical actions when acting in the world. Consequently, research participative action methodologies would need to adopt this complex and ecosystemic epistemological perspective, and adopt a «strategic invention» approach in order to clarify the concepts imported from other scientific disciplines.